Evaluating a synergistic nutritional strategy in women with polycystic ovary syndrome: a multicentric retrospective analysis - Dasgupta, Sujoy; Kumar, Priti; Biswas, Pranab Kumar; Kamat, Jayanti; Ahire, Prajakta; Fatima, Kaniz; Hadwale, Aparna; Nadkarni, Suchitra; Narvekar, Poonam; Gaitonde, Varun; Gaitonde, Milind; Motiramani, Preet R.; et al. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The objective of this study was to review clinical outcomes in women with polycystic ovary syndrome (PCOS) following 3-6 months of treatment with the marketed formulations containing insulin sensitizers, minerals, herbal extracts, amino acids, antioxidants, and vitamins. Methods: An observational study was conducted to retrospectively review clinical records of women diagnosed with PCOS (age 15-42 years; n=211) at 14 fertility clinics in India between April 2024 and February 2025. From the day of PCOS diagnosis, patients received marketed formulations containing (1) insulin-sensitizing agents, antioxidants, and vitamins and (2) fertility blend containing herbal extracts, amino acids and minerals administered as two tablets daily for 3 to 6 months. The primary outcomes assessed were improvements in PCOS symptoms such as (menstrual cyclicity, acne, and hirsutism), body mass index (BMI), waist-to-hip ratio, ovarian cyst count, hormonal profile, and clinical pregnancy rates. Results: Combination therapy significantly improved menstrual cyclicity in both obese (40% at 3 months; 80.56% at six months) and lean (42.30% at three months; 69.23% at 6 months) PCOS women. Significant reductions in acne, hirsutism, and ovarian cysts were observed across both the groups. Additionally, metabolic parameters and hormonal profiles improved significantly. The clinical pregnancy rate increased to 36.78% at three months and 65.16% at six months in obese women, while lean women showed rates of 38.46% and 53.84% respectively. Conclusions: The combination of inositols, antioxidants, herbal extracts, amino acids, minerals, and vitamins offer a promising and clinically relevant treatment option for PCOS management, demonstrating significant benefits in metabolic, hormonal, and reproductive health.